2020
DOI: 10.1177/1055665620975638
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Bone Mineral Density in Individuals With Hemifacial Microsomia: A Cone-Beam Computed Tomography Study

Abstract: Objective: The purpose of this study is to utilize cone-beam computed tomography (CBCT) to compare the bone mineral density (BMD) on the affected versus nonaffected side, among individuals with hemifacial microsomia (HFM). Methods: This retrospective study included 9 patients with HFM. Pretreatment CBCT volumes were imported into Invivo5 software, which was used to measure BMD through Hounsfield units (HU) in 3 regions of the mandible; inferior to the lower lateral incisors, inferior to the first molar and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have evaluated the morphology of the condyle in patients with CFM 1 ; however, its bone quality has not been well-studied. 2,3 To date, only one study has focused on the bone density (BD) of the mandible in patients with CFM using cone-beam computed tomography (CBCT) from an orthodontic perspective. 3 Bone mineral density describes bone quality as the mineral content in the specific volume of bone tissue with all its structures, 4 and is widely used to diagnose general bone conditions such as osteoporosis as well as locational lesions such as TMJ disease 5,6,7 Hounsfield units (HU) of multislice computed tomography (MSCT) can be used for BMD measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated the morphology of the condyle in patients with CFM 1 ; however, its bone quality has not been well-studied. 2,3 To date, only one study has focused on the bone density (BD) of the mandible in patients with CFM using cone-beam computed tomography (CBCT) from an orthodontic perspective. 3 Bone mineral density describes bone quality as the mineral content in the specific volume of bone tissue with all its structures, 4 and is widely used to diagnose general bone conditions such as osteoporosis as well as locational lesions such as TMJ disease 5,6,7 Hounsfield units (HU) of multislice computed tomography (MSCT) can be used for BMD measurements.…”
Section: Introductionmentioning
confidence: 99%
“…3 Bone mineral density describes bone quality as the mineral content in the specific volume of bone tissue with all its structures, 4 and is widely used to diagnose general bone conditions such as osteoporosis as well as locational lesions such as TMJ disease 5,6,7 Hounsfield units (HU) of multislice computed tomography (MSCT) can be used for BMD measurements. 2,8 Having a more profound understanding of bone quality in CFM may deepen our understanding of this disease and assist in its diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Their attempts to approach HFM with new measurement techniques have made progress on macroscopically understanding this disease. Tokura et al’s 8 evaluated multiple parameters of mandibular morphology based on HFM patients’ cephalometric radiographs; Elnaghy et al’s 9 found the difference between mandibular ramus bone mineral density on the affected and nonaffected side of HFM patients by cone beam computerized tomography assessments; Chen et al’s 10 investigated the cranial base involvements in HFM patients by 3-dimensional analysis, and Peng et al’s 11 characterized airway changes in HFM adolescents.…”
mentioning
confidence: 99%